As heard on TV [ popular music in advertising - Klein, Bethany (Ashgate popular and folk music series, 2009)
Through an analysis of press coverage and interviews with musicians, and licensing managers, this title considers the industrial changes that have provided a foundation for the increased use of popular music in advertising, and explores the critical issues and debates surrounding media alliances that blur cultural ambitions with commercial goals